Pemanfaatan Media Sosial Sebagai Strategi E-Bisnis Dalam Meningkatakan Penjualan Kopi Kenangan - Saragih, Hewa Angriani; Widyana, Alda; Tarigan, Anggi Zahara; Salsabila, Khairunnisa; Nurbaiti, Nurbaiti (Universitas Labuhanbatu, 2026)
This study aims to analyze the utilization of social media as an e-business strategy to increase sales at Kopi Kenangan. The research employs a descriptive qualitative method through observation, interviews, and documentation. Interviews were conducted with a staff member at the Kopi Kenangan outlet on Jalan Pancing, Medan, as well as several active consumers as primary data sources. The findings indicate that social media functions mainly as a tool for information dissemination and branding rather than a primary driver of sales. The uploaded content tends to be informative and lacks interactivity, resulting in weak consumer engagement. Consumers more frequently learn about promotions through in-store banners or the application, while purchase decisions are influenced by personal needs, strategic store location, and direct in-store experience. This study recommends optimizing interactive content, visual storytelling, and digital collaborations to enhance the effectiveness of e-business strategies.